2018
DOI: 10.1007/8904_2018_119
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning in Parents of MPS III Patients

Abstract: We report a clinically relevant impact of parenting an MPS III patient on psychosocial functioning, which is demonstrated by high levels of anxiety, depression, distress, and a remarkably high prevalence of PTSD. Structural monitoring of the psychosocial functioning of MPS III parents is therefore essential and may be beneficial for the whole family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 25 publications
3
53
0
Order By: Relevance
“…These positive outcomes are comparable to the effect of EMDR in adults with PTSD related to personal traumatic events (35). The size and persistence of the effects at follow up in our study are remarkable, especially in the context of the progressive and grim course of the disease in patients with the common phenotype of MPS III, generally causing ongoing daily stress for the whole family (4,16). Most people who are treated with EMDR are trying to cope with traumatic symptoms resulting from past events, delineated in time, in which there is a post trauma safety situation whereas parents of progressively ill children will experience multiple traumas during the course of the disease, and may even more suffer from threats of expected future medical crises and an early death.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These positive outcomes are comparable to the effect of EMDR in adults with PTSD related to personal traumatic events (35). The size and persistence of the effects at follow up in our study are remarkable, especially in the context of the progressive and grim course of the disease in patients with the common phenotype of MPS III, generally causing ongoing daily stress for the whole family (4,16). Most people who are treated with EMDR are trying to cope with traumatic symptoms resulting from past events, delineated in time, in which there is a post trauma safety situation whereas parents of progressively ill children will experience multiple traumas during the course of the disease, and may even more suffer from threats of expected future medical crises and an early death.…”
Section: Discussionsupporting
confidence: 72%
“…Earlier studies showed that IEMs have a highly negative impact on the psychosocial functioning of parents (4)(5)(6)(7), and that parents of children with IEMs report a lower health related quality of life compared to parents of other chronically ill children including paediatric cancer (8). This may be explained by the fact that parents of children with IEMs often have to deal with a continuous process of loss due to the progressive nature of the disease, facing an uncertain future with a realistic fear to lose their child often after a long diagnostic odyssey (15,16). Moreover, parents frequently face potential traumatic medical events ( e.g.…”
Section: Page 3/14mentioning
confidence: 99%
See 1 more Smart Citation
“…This study has some limitations. First, this study included parents and relatives of MPS III patients and research showed that parenting a MPS III child has great impact on the well-being of parents [ 25 , 33 , 34 ]. The impact of some of the other disorders included in ECS panels may be less severe which may have resulted in an overestimation of the potential uptake of ECS by affected families by our study.…”
Section: Discussionmentioning
confidence: 99%
“…MPS III (Sanfilippo disease) is an example of a disorder generally included in ECS panels, as it is characterized by progressive neurodegeneration resulting in cognitive decline, behavioral problems, loss of motor functions and early demise [ 24 ]. Parenting a child with MPS III strongly impacts the well-being of parents, resulting in anxiety, depression and post-traumatic stress symptoms [ 25 ]. We hypothesized that genetic and experiential knowledge on the nature of a disorder generally included in universal preconception screening panels and its potential impact on the patient and the family leads to a more positive attitude toward ECS.…”
Section: Introductionmentioning
confidence: 99%